At Home and in the Field : Ethnographic Encounters in Asia and the Pacific Islands - Mostafanezhad, Mary; Young, Forrest Wade; Mostafanezhad, Mary; Finney, Suzanne S.; Finney, Suzanne S.; Pigliasco, Guido Carlo; Pigliasco, Guido Carlo (Book collections on Project MUSE., 2015)
Crossing disciplinary boundaries, 'At Home and in the Field' is an anthology of twenty-first century ethnographic research and writing about the global worlds of home and disjuncture in Asia and the Pacific Islands. These stories reveal novel insights into the serendipitous nature of fieldwork.